Factors that affecting the prices of gold in Malaysia / Mohd Zulfadli Mohd Khalid and Siti Sarah Nasrudin - Mohd Khalid, Mohd Zulfadli; Nasrudin, Siti Sarah (Faculty of Business and Management, 2013)
This paper analyzed factors that affecting the prices of gold in Malaysia The study used Multiple Linear Regression Model to determined significant relationship between dependent and independent variables, covering data for 10 years period which are from 2003 until 2012. The researcher used three independent variables that affect the prices of gold which are crude oil prices, inflation rates and exchange rates. The empirical results have found there is negatively significant relationship between inflation rates and exchange rates on gold prices, while a crude oil price is positively significant. The results of the study are valuable for both academic and investor.